EFFECT OF GREEN MARKETING MIX ON PURCHASE INTENTION: MODERATING ROLE OF ENVIRONMENTAL KNOWLEDGE - Astuti, Kristiana; Batubara, Hani Maisyarah; Rosalina, Rosalina; Evanita, Susi; Friyatmi, Friyatmi (Jurnal Apresiasi Ekonomi, 2024)
This study investigates the moderating effect of environmental knowledge on the relationship between green marketing mix and purchase intentions. As consumer environmental awareness rises, so does the trend towards green consumption. However, a purchase intention, or willingness to buy green products, must precede actual green purchasing behavior. This research employs a quantitative survey design. Participants are randomly selected from a database of Instagram visitors and followers. A sample of 100 respondents is gathered using incidental sampling methods. Data is collected through a survey link. SEM analysis is used to analyze the data. The green marketing mix significantly impacts purchase intention, with environmental knowledge acting as a moderator. A T-test reveals a significant difference between the original sample's -0.112 and 0.000 significance values of 1.963 and 1.963, respectively. This suggests that the green marketing mix has a stronger influence on purchase intention than environmental knowledge. Keywords: Environmental Knowledge; Green Marketing Mix; Purchase Intention.